MODEL DIDAKTIK LITERASI TEKNOLOGI INFORMASI DAN KOMUNIKASI GURU SMK - Saripudin, - (2021)
ABSTRACT Currently, the advancement of information and communication technology (ICT) poses a range of opportunities and challenges, particularly in the field of technology and vocational education, and especially for teaching professionals at vocational schools. In the ICT era, the expectations of vocational school teachers are required to develop learning skills by using concepts, ideas, and viewpoints to solve ICT-based issues. This study, therefore, aims to examine the needs and assess the capacity of vocational school teachers to incorporate ICT into learning and to establish a didactic literacy model (DL). It is expected that the model established would be able to strengthen the professional skills and pedagogical knowledge of teachers in vocational schools. This research method uses Design-Based Research. Quantitative approaches are used to analyze the ICT needs of vocational teachers by involving 267 vocational teachers in West Java. Data analysis used SPSS V.23 using independent t-test and one way ANOVA, and analysis of teachers mapping index using ICT development index analysis. The results of this study show that 82% of teachers in vocational schools use the Internet network and use it to find tools for learning. The UNESCO-based ICT mapping index for West Java vocational schools is in the implementation process, where the vocational schools have an understanding of the contribution and value of the ICT application in the context of school management and learning. There are gaps in the ability to design immersive learning using multimedia in the ICT literacy skills of vocational school teachers based on gender and academic credentials in this sample, except for tenure and teacher certification status. The ability of vocational high school teachers to use ICT is based on the Personal Capacity Maturity Model (P-CMM) in Level 3 (three), which means that teachers already have a standard of mastery and understanding of the ICT and are consistent in using ICT according to the standards. Meanwhile, media production is included in level 2 (two) where teachers have repeatedly used ICT in learning but have not made it a standard in their daily activities. The model finding is DL-ICT PICE Model (Planning, Interpreting, Creating, and Evaluating) which is a DL-TIK model for the vocational teachers in integrating ICT in learning. The results of the DL-ICT PICE model implementation have shown that the technical skills and knowledge of DL-ICT teachers are in the "competent" and "good" categories, which means that vocational teachers can integrate ICT into learning "competently" and have "good" educational knowledge. This research recommends that vocational schools be reinforced at the infusion stage, namely encouraging ICT activities to be included in the learning curricula, providing ICT infrastructure for schools, and continuing coaching of teachers through training and workshops, so the demands towards teachers who have technical skills and pedagogical knowledge in the 21st century are achieved Keywords: Vocational Teachers, ICT Literacy, Didactic Model ABSTRAK Perkembangan teknologi informasi dan komunikasi (TIK) saat ini memunculkan berbagai peluang dan tantangan terutama dalam bidang pendidikan teknologi dan kejuruan, khususnya guru SMK. Tuntutan guru SMK di era TIK ini diharapkan mampu mengembangkan keterampilan pembelajaran dengan menggunakan konsep, ide, dan gagasan dalam memecahkan permasalahan dengan berbasis TIK. Oleh karena itu, penelitian ini bertujuan untuk menganalisis kebutuhan dan mengetahui kemampuan mengintegrasikan TIK dalam pembelajaran serta mengembangkan model didaktik literasi (DL) TIK guru SMK. Model yang dikembangkan ini, diharapkan mampu meningkatkan kecakapan teknis dan kecakapan pengetahuan pedagogik guru SMK. Metode penelitian ini menggunakan Design Based Research. Pada tahap analisis kebutuhan TIK guru SMK digunakan metode kuantitatif dengan melibatkan 267 guru SMK di Jawa Barat. Analisis data menggunakan SPSS V.23 dengan menggunakan independent t-test dan one way ANOVA, serta analisis indeks pemetaan SMK menggunakan analisis ICT development index. Hasil temuan penelitian ini adalah bahwa 82% guru SMK memanfaatkan jaringan internet dan digunakan untuk mencari sumber belajar. Indeks pemetaan TIK SMK di Jawa Barat berdasarkan UNESCO berada dalam tahap Applying, di mana SMK telah memiliki pemahaman tentang kontribusi dan pentingnya penerapan TIK dalam konteks manajemen sekolah dan pembelajaran. Kemampuan literasi TIK guru SMK berdasarkan jenis kelamin dan kualifikasi akademik dalam penelitian ini tidak memiliki berbedaan signifikan, kecuali masa kerja dan status sertifikasi guru terdapat perbedaan kemampuan dalam mendesain pembelajaran interaktif mengunakan multimedia. Kemampuan guru SMK dalam penggunaan TIK berdasarkan personal-capability maturity model (P-CMM) dalam level 3 (tiga), artinya guru SMK telah memiliki standar penguasaan dan pemahaman terhadap TIK yang diperlukan dan konsisten mempergunakan TIK sesuai standar. Sedangakan, pembuatan media, masuk dalam level 2 (dua), di mana guru telah berkali-kali menggunakan TIK dalam pembelajaran namun belum menjadikan sebagai standar dalam aktivitas kesehariannya. Temuan Model DL-TIK PICE (Planning, Interpreting, Creating, and Evaluating). Sebagai model DL-TIK Guru SMK dalam pengintegrasi TIK pada pembelajaran. Hasil implementasi Model DL-TIK PICE menemukan bahwa kecakapan teknis dan pengetahuan DL-TIK guru berada dalam kategori "kompeten" dan "baik", artinya guru SMK dapat mengintegrasikan TIK dalam pembelajaran secara "kompeten" dan memiliki pengetahuan pedagogik yang "baik". Penelitian ini merekomendasikan kepada SMK adanya peguatan ke tahap infusing, yaitu mendorong aktivitas TIK masuk dalam kurikulum pembelajaran, sekolah menyediakan infrastruktur TIK dan melakukan pembinaan guru secara berkesinambunagan melalui pelatihan maupun workshop, sehingga tercapai kemampuan guru yang memiliki kecakapan teknis dan pengetahuan pedagik yang menjadi tuntutan pembelajaran abad-21. Keywords: Guru SMK, Literasi TIK, Model Didaktik